Preparation and characterization of soybean protein isolate-dextran conjugate-based nanogels. (1st August 2022) - Zhang, Qing; Yue, Wenting; Zhao, Dan; Chen, Lan; Xu, Zili; Lin, Derong; Qin, Wen
Highlights: Conditions for preparing soybean protein isolate-dextran conjugate are optimized. Improvements of structural and functional properties are observed in the conjugates. Nanogels are prepared using the conjugates as materials via the self-assembly. Effects of critical parameters on particle size distribution of nanogels are studied. Nanogels with a core-shell structure are stable against heat, salt, and storage. Abstract: Soybean protein isolate (SPI)-dextran conjugate-based nanogels were prepared via the Maillard reaction combined with protein self-assembly in this study. The dextran molecular weight (40 kDa), SPI/dextran mass ratio (1:1.75), and incubation time (3.3 d) for preparing SPI-dextran conjugate (SDC) were firstly optimized. The SDC was confirmed by analyzing the changes in protein composition and infrared absorption bands and showed loosened tertiary conformation, reduced surface hydrophobicity, decreased Z-average hydrodynamic diameter (Dh ) and zeta potential, and improved emulsifying properties compared to the native SPI. Effects of conjugate concentration, pH, heating temperature, and time on Dh and polydispersity index were also evaluated. The SDC-based nanogels were translucent in aqueous solution and exhibited a spherical core-shell structure with a Dh of ∼104.4 nm and a good stability against thermal treatment, ionic strength, and storage. Results demonstrated the SDC-based nanogels possessed a potential to be used as desirable nanocarriers for encapsulating hydrophobic bioactive compounds.